Parallel Evolution of C-Type Lectin Domain Gene Family Sizes in Insect-Vectored Nematodes - Ning, Jing; Zhou, Jiao; Wang, Haixiang; Liu, Yaning; Ahmad, Faheem; Feng, Xiaohui; Fu, Yu; Gu, Xiaoting; Zhao, Lilin (Frontiers in Plant Science, 2022)
The dispersal stage of pathogens is crucial for the successful spread and infection of their hosts. Some plant-parasitic nematodes (PPNs) have evolved specialized dispersal stages to reach healthy hosts by being carried out by insect vectors. Because gene gain and loss is a major factor contributing to the evolution of novel characteristics, it is essential to clarify the gene family characteristics among nematodes with different dispersal modes to disentangle the evolution of insect-mediated dispersal. Here, the size of the C-type lectin (CTL) family genes of insect-vectored nematodes was found to be drastically reduced compared with those of self-dispersing nematodes, whereas the diversity of their functional domains was significantly higher. The gene family sizes of vector-dispersed nematodes were only a twentieth of the size of that of a self-dispersing (i.e., without a biotic vector) nematode model Caenorhabditis elegans, and these genes were inactive during the dispersal stage. Phylogenetic analysis showed that some CTL genes of vector-borne PPNs shared higher homology to the animal parasitic nematodes compared with other PPNs. Moreover, homology modeling predicted that the CTLs of insect-vectored nematodes bear remarkable structural similarity to the lectin genes of their vector's immune system. Because CTL genes are important sugar-binding proteins for the innate immune response of C. elegans, the loss of some CTL genes of vector-transmitted PPNs might be responsible for their parallel adaptations to a mutualistic relationship with their vector. These results expand our understanding of the evolutionary benefits of vector-mediated transmission for the nematode and vector-nematode co-evolution.